Adsorption of Orange II Onto Zn2Al–Layered Double Hydroxide Prepared From Zinc Ash - Tǎmaş, Andra; Cozma, Ioana; Cocheci, Laura; Lupa, Lavinia; Rusu, Gerlinde (Frontiers in Chemistry, 2020)
Dyeing industry is one of the largest water consuming industries, and in the same time generates large quantities of wastewaters. The resulted wastewaters need proper treatment before discharge, because the dyes content have a negative effect on the water body and organisms present in it. The most efficient method of waters containing dyes treatment is represented by adsorption processes. The challenge in the adsorption processes is to develop new, efficient, viable and economic adsorbent materials. Therefore, in the present paper, the performance of Zn2Al-layered double hydroxide, prepared from an industrial waste (zinc ash) as a zinc source, was investigated in the Orange II dye adsorption process. The Zn2Al-layered double hydroxide prepared from secondary sources presents similar morphological and structural characteristic with the one prepared from analytical grade reagents. The influence of initial dye concentration, adsorption time, solid : liquid ratio, pH and temperature was evaluated in order to confirm the benefit of this waste valorisation. A comparison with the reference Zn2Al-layered double hydroxide prepared from analytical grade reagents was performed and the results show that due to the small presence of impurities, the material prepared from zinc ash shows better adsorption capacities (qmax,exp = 42.5 mg/g at 293 K) than the material prepared from reagents (qmax,exp = 36.9 mg/g at 293 K), justifying the utilization of secondary sources for layered double hydroxides preparation. The proposed treatment process presents advantages from both economic and environmental protection point of view.